2016
DOI: 10.1007/s11255-016-1386-9
|View full text |Cite
|
Sign up to set email alerts
|

The new Asian modified CKD-EPI equation leads to more accurate GFR estimation in Chinese patients with CKD

Abstract: The new Asian modified CKD-EPI equation can lead to more accurate GFR estimation in Chinese patients with CKD in general practice, especially in the higher GFR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
0
42
1
Order By: Relevance
“…We compared these studies mentioned above, the inconsistent results may come from the following: (1) the research population is different. These studies, which were inconsistent with our findings, were targeted at Israel and America,(2) many of these different conclusions do not clarify the nonlinear relationship and use different regression In the present study, we found using two-piecewise linear regression model to show a nonlinear relation is different to that obtained by Lorenzo et al [7].In their study, they used subgroup analysis stratified by GFR categories to assess a U shape relation between eGFR and risk of T2DM, they used CKD-EPI equation [8] to estimate GFR, which could lead to more accurate GFR estimation in Chinese patients with CKD in general practice, especially in the higher GFR group. Because of the participants in our study was all with eGFR above 60 ml/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…We compared these studies mentioned above, the inconsistent results may come from the following: (1) the research population is different. These studies, which were inconsistent with our findings, were targeted at Israel and America,(2) many of these different conclusions do not clarify the nonlinear relationship and use different regression In the present study, we found using two-piecewise linear regression model to show a nonlinear relation is different to that obtained by Lorenzo et al [7].In their study, they used subgroup analysis stratified by GFR categories to assess a U shape relation between eGFR and risk of T2DM, they used CKD-EPI equation [8] to estimate GFR, which could lead to more accurate GFR estimation in Chinese patients with CKD in general practice, especially in the higher GFR group. Because of the participants in our study was all with eGFR above 60 ml/min/1.73m 2 .…”
Section: Discussioncontrasting
confidence: 63%
“…This website 107 Aspartate aminotransferase(AST), smoking status, drinking status, family history of diabetes, year of follow up and censor of diabetes during follow up. In our research, we added evaluated glomerular filtration rate(eGFR), which was calculated based on age, gender and Scr according to CKD-EPI equation [8]. This new Asian modified CKD-EPI equation could lead to more accurate GFR estimation in Chinese patients with CKD in general practice, especially in the higher GFR group.…”
Section: Data Source and Participants 106mentioning
confidence: 99%
“…The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation in the KSH study was developed based on Whites and Blacks, and it was later shown to introduce inaccuracies when estimating GFR in Asians [23][24][25]. In our study, we used the CMDRD equation to estimate GFR, which improved the accuracy and performance of GFR estimation in a Chinese population [26]. The mechanisms underlying the association between the serum levels of TSH and FT3 and eGFR in euthyroid individuals remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and clinical parameters of patients, including age, gender, blood pressure (BP), urinary red blood cells count, serum creatinine (SCr), urine creatinine (UCr) and 24-hour urinary protein excretion (24hUPro) were obtained immediately before renal biopsy. Estimated glomerular filtration rate (eGFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation [31]. Pathological features were evaluated according to updated Oxford classification [32] and Lee grading [33], which were graded by a pathologist blinded to patients' clinical data.…”
Section: Clinical and Pathological Manifestationsmentioning
confidence: 99%
“…Data are present as mean±SD or median (interquartile range) , or frequency in percent. equation [31] b Determined in accordance with the Oxford classification [32] Figures Figure 1 The levels of urinary joining chain containing IgG immune complexes/creatinine ratio and IgA-IgG immune complexes/creatinine ratio (OD450nm/mmol/L Cr) in patients with IgA nephropathy, patients with other kidney diseases and healthy subjects. The levels of (a) UJGCR and (b) UAGCR were significantly higher in IgAN group than HC group and DC group.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%